2021
DOI: 10.3390/ijerph18137159
|View full text |Cite
|
Sign up to set email alerts
|

Role of Quality of Life as Endpoint for Inflammatory Bowel Disease Treatment

Abstract: Inflammatory bowel diseases (IBDs) are chronic disabling conditions, characterized by an unpredictable course with flare-ups and periods of remission, that frequently affect young people and require lifelong medical follow-up and treatment. For years, the main endpoints of IBD treatment had been clinical remission and response, followed by biomarker normalization and mucosal healing. In the last decades, different therapies have been proved to be effective to treat IBD and the use of patient reported outcome (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 73 publications
0
15
0
2
Order By: Relevance
“…Previous studies have reported an association between worse abdominal symptoms and poor quality of life, and the results of our study support this. [ 22 , 23 ] Among them, the presence of visible bleeding has a significant impact on the patient’s daily life. Bloody stool is a more accurate predictor of UC activity than frequency of bowel movements [ 24 ] and may have a greater impact on DLS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported an association between worse abdominal symptoms and poor quality of life, and the results of our study support this. [ 22 , 23 ] Among them, the presence of visible bleeding has a significant impact on the patient’s daily life. Bloody stool is a more accurate predictor of UC activity than frequency of bowel movements [ 24 ] and may have a greater impact on DLS scores.…”
Section: Discussionmentioning
confidence: 99%
“…IBD can have a prolonged impact on daily functioning and earlier studies have reported lower quality of life amongst IBD patients when compared to healthy controls [ 37 ]. Further, low quality of life has been shown to be a marker of clinical[ 38 , 39 ] and mucosal disease activity [ 39 ]. Thus, the association between personality and disease-related quality of life is highly relevant for IBD patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that UC impairs QoL and clinical activity (increased bowel frequency, urgency, and rectal bleeding) was pointed out as the factor with the most negative impact on HRQoL ( 22 – 24 ). Moreover, treatments usually used in trials and clinical practice (as aminosalicylates, biologics, and small molecules) are able to improve de QoL in patients with UC ( 25 ). The Inflammatory Bowel Disease Questionnaire 32 (IBDQ-32) [a 32-item questionnaire that includes four aspects of the patient’s life and the main domains are intestinal symptoms (10 items), systemic symptoms (five items), and social (12 items) and emotional domains (five items)] and Inflammatory Bowel Disease Questionnaire 36 (IBDQ-36) [a 36-item questionnaire that comprises these points: intestinal symptoms (eight items), systemic symptoms (seven items), social (six items) and emotional domains (eight items), and functional impairment (seven items)] are the most commonly disease-specific tools used and have been demonstrated to be reliable and valid ( 26 ).…”
Section: Clinical Target For Disease Clearance In Ucmentioning
confidence: 99%